Ekstraksi Benda Asing pada Kavum Nasi Melalui Bronkoskopi: [Extraction of Nasal Cavity Foreign Object using Bronchoscopy] - Isnu Pradjoko; Chandra Jaya (Jurnal Respirasi, 2018)
Background: Aspiration of a tracheobronchial foreign body is a serious and fatal event. Progress in terms of prevention, first aid, and endoscopic technology, caused a decline of almost 20% of deaths from foreign body aspiration that occurred in the United States. Statistically, the percentage of foreign body aspirations based on their respective location is: 5% hypopharynx, 12% larynx-trachea, and 83% bronchus. Most cases of foreign body aspiration occur in children aged <15 years old; about 75% of foreign body aspirations occur in children aged 1-3 years. The female-to-male ratio is 1.4:1. Case: A 11-year-old boy swallowed needles while playing flashlight about 2 hours before coming to Pulmonary Emergency Room of Dr. Soetomo General Hospital. Discussion: Chest X-ray examination found a shadow of metal density projected in the right lung. Fiber optic bronchoscopy (FOB) was performed for diagnostic and therapeutic indication to see the presence of a foreign body in the airway and remove the foreign body, but failed. When the needle was extracted, the patient coughed that the needle bounces to the supramaxilla area. FOB with nasal cavity approach successfully extracted the corpus alienum. Conclusion: Corpus alienum of airway sometimes is difficult to extract. FOB with nasal cavity approach can be done to manage corpus alienum in the upper airway that moved from lower airway when FOB was performed.